Zarządzanie strategiczne: małe versus duże przedsiębiorstwa - Łobos, Krzysztof; Sus-Januchowska, Aleksandra (Strategic Management: Small versus Large Enterprises, 2008)
This paper is focused on differences between strategic management process in small and large companies. Distinctions which are mentioned concern mainly the strategic planning and the implementation of strategy. Moreover, the article emphasizes the strategic flexibility and the discrete as features more constructive and useful for small than large organizations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 209-215